Optical Band Gap of PMMA: Cody, ASF, and DASF Methods Compared to Tauc - Allif Rosyidy Hilmi; Yofinda Eka Setiawan; Nailul Hasan (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2026)
This study aimed to determine the optical band gap of polymethyl methacrylate (PMMA) using alternative methods to the conventional Tauc plot. PMMA was prepared by solution casting and characterized using UV–Vis spectroscopy. The optical band gap was approximated by applying the Cody, Absorption Spectrum Fitting (ASF), and Derivative ASF (DASF) methods, and the results were compared with those from the Tauc approach. The optical band gap values ranged from 3.10 eV to 4.94 eV, which fall within or near the range reported in the literature for PMMA, depending on the analysis method and transition model used. Each method had distinct advantages: the Cody method provided a clearer linear region for amorphous systems, ASF offered a practical approach that did not require sample-thickness information, and DASF enhanced precision through derivative-based analysis. The observation of band gap values corresponding to both direct and indirect optical transitions suggests the presence of multiple effective optical transition pathways in amorphous PMMA. These findings demonstrate that the Cody, ASF, and DASF methods can serve as reliable alternatives to the Tauc method for analyzing the optical properties of polymeric materials.